Group Supervision:: A reflective and creative space - Falzon, Rose (European Journal for Qualitative Research in Psychotherapy, 2014)
In this article, I enquire about the perception and use of creativity and innovation in group supervision, taking into account also the setting and culture one works in.I come from the cultural framework of a densely populated small island, embracing both the westernized realm as well as that created through the multi-layered historical and social traditions. The following are experiential narratives from supervisors and supervisees, working in diverse settings but in the same tight community. All names and some particular aspects leading to any identification were changed to protect confidentiality.